Panopticon Strategy in Juvenile Delinquency Regulation and Rehabilitation in Indonesia - Diana Lukitasari; Hartiwingsih Hartiwingsih; Subekti Subekti; Lushiana Primasari; Dian Esti Pratiwi (IJCLS (Indonesian Journal of Criminal Law Studies), 2024)
This study addresses juvenile delinquency in Indonesia through a combined legal and social analysis, proposing innovative solutions for sustainable impact. Drawing inspiration from Michael Foucault's Panopticon theory, the study examines how Law Number 1 of 2023 on the Criminal Code interacts with evolving social dynamics. It advocates for a flexible legal framework that not only punishes but also emphasizes rehabilitation and social reintegration for adolescents. The research underscores the critical need for legal reforms that adapt to changing societal norms and challenges posed by information technology. It explores the influence of unrestricted digital media access on adolescent behavior, including phenomena like klithih, which reflects community and peer influences. The study's findings highlight the pivotal role of family, peers, and community in shaping youth behavior and calls for enhanced community-based education and supervision strategies. Consequently, the study proposes recommendations for a more humane and effective legal approach to juvenile delinquency. These include prevention strategies that empower communities in educating and monitoring young people. By advocating for a holistic and evidence-based approach, this research aims to inspire policymakers, legal practitioners, and the public to foster a supportive environment for Indonesian youth, paving the way for a brighter future.